Integrated and spatially explicit modelling of the economic value of complex environmental change and its indirect effects - Ian Bateman; Amy Binner; Emma Coombes; Brett Day; Silvia Ferrini; Carlo Fezzi; Michael Hutchins; Paulette Posen (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2012)
Arguably the greatest challenge to contemporary research is to capture the inter-relatedness and complexity of the real world environment within models so at to better inform decision makers of the accurate and complete consequences of differing options. The paper presents an integrated model of the consequence of climate change upon land use and the secondary and subsequent effects arising subsequently. The model predicts the shift in land use which climate change is likely to induce and the impacts upon farm gross margins arising from this. However, both the direct driver of climate change and the induced shift in land use patterns will cause secondary effects upon the water environment for which agriculture is the major source of diffuse pollution. We model the consequent impact of changes in such pollution upon water ecology showing that these will be spatially specific and significant. These impacts are likely to cause further knock-on effects upon the recreational benefits of water environments and these are assessed using a spatially explicit revealed preference database. Taken together this analysis permits a holistic examination of a much wider range of effects and net value consequences arising from climate change impacts upon land use.
Keywords: 330; integrated modelling; economic valuation; land use; water; recreation